Safety assessment and antimicrobial potential of Enterococcus spp. isolated from raw goat milk and cheese - Grujović Mirjana Ž.; Žugić-Petrović Tanja; Marković Katarina G. (Kragujevac Journal of Science)
This study aimed to assess the safety and antimicrobial properties of Enterococcus species isolated from raw goat milk and cheese. The isolates were evaluated for hemolytic activity on blood agar plates and antibiotic susceptibility by determining the minimum inhibitory concentrations (MICs) of five antibiotics: ampicillin, tetracycline, gentamicin, streptomycin, and vancomycin. Furthermore, the antagonistic activity of the Enterococcus strains against indicator bacteria was assessed using the agar-well diffusion method. Hemolytic activity results demonstrated a-hemolysis in all isolates. Among the 71 Enterococcus isolates examined, 32.39% exhibited resistance to at least one antibiotic, with resistance profiles varying between species. Enterococcus faecalis isolates predominantly showed resistance to vancomycin, ampicillin, tetracycline, and gentamicin, while Enterococcus faecium and Enterococcus hirae displayed resistance to vancomycin with different susceptibility patterns to the other antibiotics. The antagonistic assays revealed a broad spectrum of inhibitory effects, with variation in inhibition zone diameters. These findings provide valuable insights into the safety and antimicrobial potential of Enterococcus spp. from raw goat milk and cheese and give an insight into their potential applications in the food industry.